Meningkatkan Keterlibatan Siswa di Kelas Menggunakan Model Pembelajaran Think Pair Share - Arlina; Hasibuan, Raudhatul Ma'wa; Syahida, Nadila Aulia; Aqilla, Najla Puteri; Aulaz, Ibnu (At-Tadris: Journal of Islamic Education, 2023)
There is still low student learning participation. There has not been an application of a learning model that attracts students and can foster active student learning participation and students also still find it difficult to understand the material being learned during learning. The data collection techniques used in this study were observation and documentation. Qualitative data analysis techniques to determine how much student learning participation has increased. In this Class Action Study, researchers plan 2 cycles of action using the Kemmis and Mc Taggart model research procedures. Kemmis and Mc Taggart's model research begins with planning then action, observation and reflection. The hypothesis in this study is that the use of the Think Pair Share learning model can increase student learning participationThe Think-Pair-Share strategy is a group discussion strategy which is a participatory pedagogic concept through social interaction, togetherness, and action-oriented communication explaining that TPS is a learning method developed by combining independent and group learning methods. With this TPS, students will be helped in changing the positive behavior in communication skills that occurs when they listen to each other and bring out mutual respect. Think Pair Share learning model activities can develop the thinking of individual students because of the thinking time, so that the quality of answers can also increase. By using the Think Pair Share type cooperative learning learning model, before discussing in groups, students try to think first, then discuss with their partners so that students already have material to bring in group discussions. This can be a strong factor in improving students' ability to respond to questions and foster an attitude of mutual help to each other. Thus, students will be actively involved in the learning process and can improve learning outcomes.